2022
DOI: 10.7717/peerj.12858
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian computation for the common coefficient of variation of delta-lognormal distributions with application to common rainfall dispersion in Thailand

Abstract: Rainfall fluctuation makes precipitation and flood prediction difficult. The coefficient of variation can be used to measure rainfall dispersion to produce information for predicting future rainfall, thereby mitigating future disasters. Rainfall data usually consist of positive and true zero values that correspond to a delta-lognormal distribution. Therefore, the coefficient of variation of delta-lognormal distribution is appropriate to measure the rainfall dispersion more than lognormal distribution. In parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The coefficient of variation (CV) is the ratio of the standard deviation to the mean, which is a measure of the variability relative to the mean. It is free of units of measurement and is often used to measure the dispersion of data and to compare them with each other [74][75][76]. In this paper, it is used to reflect the degree of dispersion of the ARSEI and to assess the inter-annual time series stability of the ARSEI.…”
Section: Time Series Stability Analysismentioning
confidence: 99%
“…The coefficient of variation (CV) is the ratio of the standard deviation to the mean, which is a measure of the variability relative to the mean. It is free of units of measurement and is often used to measure the dispersion of data and to compare them with each other [74][75][76]. In this paper, it is used to reflect the degree of dispersion of the ARSEI and to assess the inter-annual time series stability of the ARSEI.…”
Section: Time Series Stability Analysismentioning
confidence: 99%
“…Several researchers have investigated rainfall dispersion in Thailand, such as Kumphon et al [3], Szyniszewska and Waylen [4], and Thodsan et al [5]. Additionally, studies on statistical inference for rainfall distribution in Thailand have been reported by Maneerat et al [6], Khooriphan et al [7], Yosboonruang et al [8,9], and Thangjai et al [10]. Previous research on statistical inference has primarily focused on measuring rainfall dispersion using variance and coefficient of variation.…”
Section: Introductionmentioning
confidence: 99%
“…The lognormal distribution plays a significant role in climate change studies due to its ability to model skewed data, analyze extreme events, quantify uncertainty, and facilitate econometric analyses. According to the rainfall data, several researchers have reported that the data follow a lognormal distribution with zero values, also known as a deltalognormal distribution [8,9,[25][26][27][28]. The delta-lognormal distribution consists of positive values following a lognormal distribution and actual zero values following a binomial distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several researchers have proposed confidence intervals for various functions of the DLN distribution, such as the mean, coefficient of variation, and percentile. For instance, Maneerat et al [14], Maneerat et al [15], Yosboonruang et al [16], and Thangjai et al [17] have all explored this topic.…”
Section: Introductionmentioning
confidence: 99%